2015
DOI: 10.3386/w21806
|View full text |Cite
|
Sign up to set email alerts
|

Double for Nothing? Experimental Evidence on the Impact of an Unconditional Teacher Salary Increase on Student Performance in Indonesia

Abstract: Sabon (and the team at puslitjak), Dhani Nugaan, Bastari, Hari Setiadi, Rahmawati, and Yani Sumarno (and the team at puspendik), who supported this experiment and implemented it flawlessly. Over the years, the project also benefited from excellent research assistance of Ai Li Ang, Husnul Rizal, and others at the World Bank office in Jakarta. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the National Burea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 27 publications
1
45
2
1
Order By: Relevance
“…A policy change in Indonesia permanently doubled salaries for teachers who met certain certification criteria, and de Ree, Muralidharan, Pradhan and Rogers (2015) use a randomized phase-in design across a large sample of teachers to evaluate the program. They find teacher satisfaction increased, but there was no discernable impact on teacher effort or student learning two to three years after the reform.…”
Section: Pupil/teacher Ratios and Teacher Paymentioning
confidence: 99%
“…A policy change in Indonesia permanently doubled salaries for teachers who met certain certification criteria, and de Ree, Muralidharan, Pradhan and Rogers (2015) use a randomized phase-in design across a large sample of teachers to evaluate the program. They find teacher satisfaction increased, but there was no discernable impact on teacher effort or student learning two to three years after the reform.…”
Section: Pupil/teacher Ratios and Teacher Paymentioning
confidence: 99%
“…This training increased pedagogical quality, but failed to improve students' cognitive skills [10]. Another experiment in Indonesia encouraged teachers to become certified in exchange for a doubling of their salary [11]. Again, even though the presence of certified teachers increased, the authors found no effect of the program on student learning.…”
Section: Training and Certificationmentioning
confidence: 84%
“…The certification program in the Indonesian study was limited to submission of a teaching portfolio and two weeks of training, making it far more limited in scope than typical multiyear pre-service certification programs. Additionally, the bundling of certification with a salary increase of 100% makes it difficult to attribute the (null) effects of the program to certification itself [11].…”
Section: Limitations and Gapsmentioning
confidence: 99%
“…A closely related paper is de Ree et al (2016), who show that an unconditional salary increase among teachers in India had no effect on performance. There are a number of papers on performance pay for public service providers (Muralidharan and Sundararaman2011; Gertler and Vermeersch2013; Glewwe et al.2010; Khan, Khwaja and Olken 2016).…”
mentioning
confidence: 99%